Unveiling the hidden: identification and management of overlooked blood vessels in laparoscopic left hemicolectomy for splenic flexure cancer - Wenjun Luo; Peng Chen; Qiang Du; Lie Yang; Zongguang Zhou (BMC Surgery, 2024)
Abstract Background During laparoscopic left hemicolectomy procedures, a previously overlooked consistently thick blood vessel within the gastrocolic ligament near the splenic hilum may contribute to post-operative bleeding complications. The purpose of this study was to investigate the identification and management of the previously overlooked blood vessel. Methods This is a retrospective descriptive study of patients undergoing laparoscopic left colectomy for splenic fexure cancer conducted at a national gastrointestinal surgery centre in China. Consecutive patients with splenic fexure cancer who underwent laparoscopic left colectomy using our“five-step process”(n = 34) between January 2021 and July 2023 were included. Results The vessels can be effectively exposed using the aforementioned “five-step process.” It was observed that the overlooked vessels consistently present in all patients were identified as the omental branch of the left gastroepiploic artery and vein. Conclusion We have identified the origin of previously overlooked blood vessels and recommended a safe method for their management. This may offer advantages to colorectal surgeons performing laparoscopic left colectomy for splenic flexure cancer